ANALISIS NILAI PERUSAHAAN PADA PERUSAHAAN TEKSTIL DAN GARMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Naufal Dzaki Ramadhany; Rahman Amrullah Suwaidi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
The value of the company is something that is very important for the company, this isbecause an increase in stock prices will reflect the prosperity of investors or shareholders,a high company value indicates that the company's performance is good. This study aims toanalyze, test and prove empirically the leverage, profitability, and liquidity of the firmvalue of textile and garment companies on the Indonesia Stock Exchange in 2016-2019.The population in this study are Textile and Garment companies listed on the IndonesiaStock Exchange as many as 18 companies. The sampling technique used was purposivesampling technique in order to obtain a sample of 12 companies based on predeterminedcriteria. The data analysis method used is multiple linear regression. Based on the resultsof the study, it shows that Leverage as proxied by the Debt to Equity Ratio (DER) does notcontribute to the Value of the Textile and Garment Sub-Sector Companies listed on theIndonesia Stock Exchange (IDX) in 2016-2019. Meanwhile, profitability as proxied byReturn On Assets (ROA) and liquidity as proxied by Current Ratio (CR) contributed to theValue of Textile and Garment Sub-Sector Companies listed on the Indonesia StockExchange (IDX) in 2016-2019.